Video Game Representations as Cues for Collaboration and Learning - Sharritt, Matthew J; Suthers, Daniel D (International journal of gaming and computer-mediated simulations, 2009)
Literature suggests that games can support learning in schools by enabling creative problem solving, allowing dynamic resource allocation, by providing a motivating, immersive activity, and by supporting explorations of identity. A descriptive, inductive study was carried out to identify how high school students in a school setting make use of the video game interface and its representations. Results demonstrate that specific cues direct attention, helping to focus efforts on new or underutilized game tasks. In addition, consistent and well-organized visualizations encourage learning and collaboration among students by providing shared referential resources and scaffolding coordinated sequences of problem solving acts during gameplay. Conversely, when affordances are inconsistently represented, students’ focus can shift from problem solving at the goal level (game strategy, etc.) to problem solving why the game interface is frustrating their goals. In general, the design of game representations and behaviors can help guide or hinder student learning.